2017
DOI: 10.3390/nu9040405
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Consumption in the Development of Obesity and the Effects of Different Protocols of Physical Exercise on the Hepatic Metabolism

Abstract: Fructose consumption has been growing exponentially and, concomitant with this, the increase in the incidence of obesity and associated complications has followed the same behavior. Studies indicate that fructose may be a carbohydrate with greater obesogenic potential than other sugars. In this context, the liver seems to be a key organ for understanding the deleterious health effects promoted by fructose consumption. Fructose promotes complications in glucose metabolism, accumulation of triacylglycerol in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 133 publications
(177 reference statements)
1
95
1
6
Order By: Relevance
“…On the other hand, high fructose consumption (HFC) leads to increased body weight with elevated systolic blood pressure, blood glucose, insulin, and serum triglyceride (TG) levels [7]. HFC reduces energy expenditure, thereby causing obesity, adipocyte hypertrophy, and inflammation [8]; lipid spillover further causes hepatic steatosis, peripheral insulin resistance and diabetes, raised levels of LDL and a decrease in HDL [9]. Furthermore, HFC elicits elevation of certain pro-inflammatory serum proteins [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, high fructose consumption (HFC) leads to increased body weight with elevated systolic blood pressure, blood glucose, insulin, and serum triglyceride (TG) levels [7]. HFC reduces energy expenditure, thereby causing obesity, adipocyte hypertrophy, and inflammation [8]; lipid spillover further causes hepatic steatosis, peripheral insulin resistance and diabetes, raised levels of LDL and a decrease in HDL [9]. Furthermore, HFC elicits elevation of certain pro-inflammatory serum proteins [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that fructolysis (with the help of specific enzymes: fructokinase, aldolase B, and trio kinase) takes place mainly in the liver resulting in the production of other biomolecules that includes glucose (29–54%), lactate (25%), and triglycerides and glycogen (15–18%) . Consequently, increased fructolysis leads to accumulation of triglycerides (adipose tissues and intramuscular triglycerides) that are important causes of obesity in both adults and baby humans . With frustrated process of fructolysis in the treated animals (both OT and UAV treated) via a mechanism yet to be understood, fructose levels in blood are elevated as observed in Raman spectroscopic results reported here.…”
Section: Resultsmentioning
confidence: 99%
“…Current studies have shown that consumption of fructose changes the lipid profile . Incir et al noticed an increase in serum triglyceride, TC, and LDL levels and a decrease in HDL levels in the fructose‐treated group.…”
Section: Discussionmentioning
confidence: 99%